2020
DOI: 10.2147/cmar.s237726
|View full text |Cite
|
Sign up to set email alerts
|

<p>OIP5-AS1/miR-137/ZNF217 Axis Promotes Malignant Behaviors in Epithelial Ovarian Cancer</p>

Abstract: Background: Long non-coding RNAs (lncRNAs) have been reported to play crucial regulatory roles in cellular activities and are associated with the carcinogenesis of various diseases. OIP5-AS1, as a novel lncRNA, function in epithelial ovarian cancer (EOC) still remains unclear. Material and Methods: qRT-PCR and Western blot analyses were performed to measure relevant expression, as needed. A series of functional experiments were performed to determine the role of OIP5-AS1 in EOC cells. Luciferase report, RNA pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Bai and Li ( 39 ) stated that cell proliferation and migration were impeded, while more apoptotic cells were induced, following the silence of OIP5-AS1 in gastric cancer. Knockdown of OIP5-AS1 restrained cell viability, migration, invasion and induced apoptosis in OC cells during the current study, which agrees with the results of OIP5-AS1 in other OC research ( 16 , 17 ). The link between OIP5-AS1 and glycolysis has yet to be reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bai and Li ( 39 ) stated that cell proliferation and migration were impeded, while more apoptotic cells were induced, following the silence of OIP5-AS1 in gastric cancer. Knockdown of OIP5-AS1 restrained cell viability, migration, invasion and induced apoptosis in OC cells during the current study, which agrees with the results of OIP5-AS1 in other OC research ( 16 , 17 ). The link between OIP5-AS1 and glycolysis has yet to be reported.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, OIP5-AS1 knockdown restrains CCAAT/enhancer-binding protein α and TNF receptor-associated factor 4 levels to retard glioma cell growth via binding to miR-367-3p ( 15 ). OIP5-AS1 is reported to be overexpressed in OC and facilitates the malignant tumor growth and metastasis of OC by the miR-137/ZNF217 or miR-324-3p/NFIB axis ( 16 , 17 ). However, the regulation in glycolytic process of OC and other regulatory mechanisms underpinning OIP5-AS1 remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It suppressed apoptosis in vitro and could enhance tumor growth and metastasis in vivo in nude mice [ 157 , 158 ] ( Table 2 ). OIP5-AS1 functioned as a ceRNA competing with NFIB (Nuclear factor I B) and ZNF217 (Zinc finger protein 217) for binding miR-324-3p or miR-137, respectively [ 157 , 158 ]. An axis OIP5-AS1/miR-324-3p/NFIB was demonstrated using qRT-PCR, Western blotting, and the dual-luciferase reporter assay [ 157 ].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…An axis OIP5-AS1/miR-324-3p/NFIB was demonstrated using qRT-PCR, Western blotting, and the dual-luciferase reporter assay [ 157 ]. The OIP5-AS1/miR-137/ZNF217 axis was validated via luciferase reporter, RNA pull-down, and RIP assays [ 158 ]. OIP5-AS1 promoted OvCa tumor growth and metastasis by upregulating either ZNF217 through binding and inhibiting of suppressor miR-137 or NFIB by dint of binding of suppressor miR-324-3p [ 157 , 158 ].…”
Section: Oncogenic Lncrnas As Cernas In Ovarian Cancermentioning
confidence: 99%
“…Current study has shown that OIP5-AS1 was up-regulated in breast cancer which regulates the expression of ZEB2 by acting as competitive endogenous RNA (ceRNA) for miR-340-5p, and then promotes metastasis of breast cancer 27 . Similarly, OIP5-AS1 regulated ovarian cancer progression via miR-137/ZNF217 axis 28 . Knockdown of OIP5-AS1 up-regulates miR-410 to specifically block Wnt-7b/β-catenin pathway, thereby inhibiting the growth, invasion and migration of glioma cells, and promoting their apoptosis 29 .…”
Section: Introductionmentioning
confidence: 97%